2010
DOI: 10.1007/s10551-010-0504-3
|View full text |Cite
|
Sign up to set email alerts
|

Leading and Following (Un)ethically in Limen

Abstract: liminality, ethical leadership, ethical followership, ethical processes, gray areas,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 78 publications
0
13
0
1
Order By: Relevance
“…Identity work has been used in organisation studies as a useful lens through which to explore positions of change or ambiguity for both individuals and enterprises. For instance, Cunha et al (2010) note the challenges that arise in organisations as struggles occur between internal communities over ethical norms. Tensions, particularly in terms of structure and resistance to that structure, are also found by Meira (2014) in an organisation following its take-over by employees.…”
Section: Identity Work In Relation To Communitiesmentioning
confidence: 99%
“…Identity work has been used in organisation studies as a useful lens through which to explore positions of change or ambiguity for both individuals and enterprises. For instance, Cunha et al (2010) note the challenges that arise in organisations as struggles occur between internal communities over ethical norms. Tensions, particularly in terms of structure and resistance to that structure, are also found by Meira (2014) in an organisation following its take-over by employees.…”
Section: Identity Work In Relation To Communitiesmentioning
confidence: 99%
“…Other studies have denoted that entire organizations can go through liminal phases during periods of change (Cunha et al, 2010;Czarniawska & Mazza, 2003;HowardGrenville et al, 2011;Powley, 2009;Powley & Piderit, 2008;Wagner et al, 2012). These liminal phases can be triggered by external events.…”
Section: Liminality As a Processmentioning
confidence: 99%
“…Wagner et al (2012) argued that an organizational liminal phase can be triggered through the creation of an internal project team assigned to develop and implement a specific change initiative (Wagner et al, 2012). Moreover, behavior that threatens the prevailing ethical norms in an organization can also challenge and decompose organizational structures and cause a temporary liminal phase (Cunha et al, 2010). Furthermore, Howard-Grenville et al (2011) found that an organization's employees can intentionally craft "experiences that bring forward new approaches and invite different interpretations that hold potential for altering the cultural order" in an organization (Howard-Grenville et al, 2011: 2).…”
Section: Liminality As a Processmentioning
confidence: 99%
“…In practice, there are many factors influence the revolution of school administrative, the important issue in this is "the practices of the principal leadership". The success of the school reconstruction relies on not only the organizational structure change but the principal's behavior of ethical leadership (Avey, Palanski, and Walumbwa, 2011;Cunha, Guimaraes-Costa, Rego, Clegg, 2010;Davies and Ellison, 1997;Lee and Cheng, 2011). In this paper, we not only fill the gap of the behavior side of the practices of the ethics which is the consequences variables in the paper.…”
Section: Introductionmentioning
confidence: 94%